1998
DOI: 10.1295/polymj.30.37
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Wood Pulp Treated by 55 wt% Aqueous Calcium Thiocyanate Solution

Abstract: ABSTRACT:Attempt was made to clarify the structural change of wood pulp during the treatment of concentrated aqueous (aq) calcium thiocyanate (aq Ca(SCN)z) solution at room temperature. For this purpose, X-ray, DSC, and CPIMAS 13 C NMR were used to measure changes of crystalline structure and formation of cellulose-solvent complex. X-Ray data indicated that 55 wt% aq Ca(SCN)2 so ln. causes intracrystalline interplanar swelling of the wood pulp, forming cellulose--calcium thiocyanate addition compound. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…5 Such molecular adducts of cellulose have been reported also for aq lithium thiocyanate 6 and aq zinc chloride solutions. 7 However, the structures of all these cellulose adducts have not been clear yet.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…5 Such molecular adducts of cellulose have been reported also for aq lithium thiocyanate 6 and aq zinc chloride solutions. 7 However, the structures of all these cellulose adducts have not been clear yet.…”
mentioning
confidence: 78%
“…LJH might include contribution from energies necessary to form adducts with cellulose and break hydrogen bonds within cellulose solid. 5 The above formula could explain the fact that LJH is 0 for aq Ca(NCS)z solution with Ccar = 48.5 wt% (stable 4 hydrate type) and becomes larger when aq Ca(NCS)z solution with higher CcaT (hydration number is less than 4) interacts with cellulose so as to satisfy 4 hydrates-like thiocyanate. In other words, cellulose might act as a supplier of R-0-R moiety like water (H-0-H moiety) directly interacting with aq Ca(NCS)z with evolution of heat.…”
Section: Structure Of Aq Calcium Thiocyanate Solution Capable Of Dissmentioning
confidence: 97%
“…The insoluble CP sample shows no peak during heating, but the soluble sample CAR-2, cellulose regenerated from cuprammonium soln., reveals an endothermic peak near dissolution temperature. In the previous paper 12 we reported that cellulose-55 wt% aq Ca(SCN)z soln. exhibits an exothermic DSC peak attributable to cellulose-aq Ca(SCN)2 complex formation far below the dissolution temperature and shows no peak near the actual dissolving temperature.…”
Section: Solubility Of Various Celluloses In Aq Calcium and Sodiummentioning
confidence: 92%
“…In water, only cellulose II is recovered, but in methanol the product is mainly cellulose I. Upon precipitation in acetone the product is amorphous [77]. The interaction between cellulose and salt hydrates have also been examined using Raman spectroscopy [74], and of course different NMR spectroscopy techniques [78].…”
Section: Molten Inorganic Salt Hydrates/concentrated Inorganic Salt Smentioning
confidence: 99%